ANALISIS FAKTOR YANG MEMPENGARUHI PENENTUAN LOKASI TERMINAL TIPE A DARI AIA PACAH KE ANAK AIR KECAMATAN KOTO TANGAH KOTA PADANG - Loli Fitria; Endah Purwaningsih (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study purpose to find out (1) the factors that caused the transfer of type A terminal locations from Aia Pacah to Anak Air in Koto Tangah Subdistrict, Padang City, (2) factors for type A terminal location selection in Anak Air, Batipuh Panjang Village, Koto Tangah District, Padang City. This type of research is qualitative descriptive. The research subject was determined by purposive sampling technique with the consideration that the person was considered the most knowledgeable about the object of research so that there were 5 informants with descriptions of one person from the Padang City Transportation Agency, one person from the Public Works and Spatial Planning Office of Padang and three people from the Planning and Development Agency Padang city. Based on the research, it is known that the causes of the transfer of type A terminal locations from Aia Pacah to Anak Air are (1)the terminal location far from the city service center , (2) lack of supporting facilities and infrastructure and (3) earthquake disaster. Whereas the factors for selecting the location of type A terminals in Anak Air, Batipuh Panjang Village are (1) terminal locations connected with arterial roads, (2) terminal locations related to AKAP, AKDP, and railway lines, and (3) locations close to the city service center.